Orthopaedics and Fractures: lecture notes - Duckworth, T. (Lecture notes, 2010)
Providing a concise approach to the subject, the new edition of Lecture Notes: Orthopaedics and Fractures reflects recentchanges to medical education and includes new management techniques. Divided into two major sections, 'General Principles'covers form and function, fractures, trauma and musculo-skeletaldisorders; while 'Regional Orthopaedics' covers the examination ofand conditions affecting individual regions of the body i.e. footand ankle, spine and trunk. This ensures the content is integratedto allow better and easier navigation. Featuring an extensive collection of X-rays and photographs oforthopaedic conditions, Lecture Notes: Orthopaedics andFractures is ideal for any medical students, junior doctors,nurses or allied health professionals who want a core introductionto this important specialty.